(untitled) (American Journal of Technology and Applied Sciences, 2026)
In this article the system of forces generated by operation of drilling bits at angles of vertical (0°), 15° and 30° inclinations of mining enterprises is analyzed. A mathematical model of the axle load (WOB), side force (Side Force), frictional force and the oblique angle of normal force was developed on the basis of a trigonometric approach and their effect on the normal operation of the bullet was determined. The results of the study show that slope angles from 15° to 30° reduce the axle load by 3.4-13.4%, and increase the side force by 25.9-50%. This condition significantly changes the drilling velocity, drill speed, and stabilizer load. The article provides recommendations based on modern Scopus index scientific sources.